FRESHWATER SHRIMPS OF THE COLOMBIAN TRIBUTARIES OF THE AMAZON AND ORINOCO RIVERS (PALAEMONIDAE, EURYRHYNCHIDAE, SERGESTIDAE) - Valencia Diego; Campos Martha (Caldasia)
A review of freshwater shrimps belonging to the genera Palaemonetes,Pseudopalaemon, Euryrhynchus and Acetes of the Colombian tributaries of theAmazon and Orinoco Rivers is presented. The species found in this work arerecorded for the fi rst time for Colombia: Palaemonetes ivonicus Holthuis, 1950,Palaemonetes mercedae Pereira, 1986, Pseudopalaemon amazonensis Ramos-Porto,1979, Pseudopalemon chryseus Kensley & Walker, 1982, Euryrhynchus amazoniensisTiefenbacher, 1978 and Acetes paraguayensis Hansen, 1919. Diagnoses, illustrations,distributional data and a key to the families, genera and species are presented.